Application of ICT-Based Media in Islamic Religious Education Learning - Abdul Ghofur; Abdul Mu’id; Ida lutfiyatul Jamilah (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2025)
This study aims to evaluate the efforts of Islamic Religious Education teachers at SMK Sunan Ampel Menganti in utilizing ICT-based learning media, understanding the utilization of the media, and analyzing the quality of Islamic Religious Education at the school, which is located in Gresik Regency, East Java. This type of research is descriptive-qualitative. The data used consists of primary and secondary data. The research instruments include observation guidelines, interviews, and documentation. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis is carried out with steps that include data reduction, data presentation, drawing conclusions, and verifying the validity of the data. The results of the study indicate that: (1) the efforts of Islamic Religious Education teachers in using ICT-based learning media include: first, initial preparation for using the media; second, preparation of ICT-based learning media; third, steps for utilizing the media; fourth, implementation of learning using ICT-based media; and fifth, the results of using ICT-based learning media. (2) The process of utilizing media in Islamic Religious Education learning by teachers includes: initial preparation by compiling lesson plans, preparing ICT-based media, and conveying learning objectives. (3) The quality of PAI learning implemented through ICT-based media helps teachers to deliver material effectively and efficiently, makes it easier for students to understand lessons, opens up scientific knowledge, and provides opportunities for students to study outside of school for longer periods, with the hope of improving student learning achievement